1992
DOI: 10.1091/mbc.3.8.839
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the gene for the gap junctional protein connexin43 and expression of functional cell-to-cell channels are regulated by cAMP.

Abstract: We investigated the mechanism by which cyclic AMP (cAMP) induces gap junctional communication via cell-to-cell channels in a communication-deficient rat Morris hepatoma cell line. We found that under basal conditions, the cells transcribe cx43 at a low level but do not transcribe cx26 or cx32. Elevation of intracellular cAMP, which induced communication, increased cx43 mRNA 15-to 40-fold and the rate of cx43 transcription 6-fold. Cx43 protein was detected by immunostaining in junctions of only those cells in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 39 publications
3
60
0
2
Order By: Relevance
“…CAMP elevating agents, like forskolin, have been described to function as gap junction up-regulators, 30 and indeed, we observed an increase in calcein transfer/ FACS in the gap junction-competent cell lines we tested. Surprisingly however, forskolin did not increase the BSE but rather enhanced tumor proliferation (Table 4), because it inhibited GCV toxicity in the hTK + cells.…”
Section: Discussionsupporting
confidence: 72%
“…CAMP elevating agents, like forskolin, have been described to function as gap junction up-regulators, 30 and indeed, we observed an increase in calcein transfer/ FACS in the gap junction-competent cell lines we tested. Surprisingly however, forskolin did not increase the BSE but rather enhanced tumor proliferation (Table 4), because it inhibited GCV toxicity in the hTK + cells.…”
Section: Discussionsupporting
confidence: 72%
“…The ability of cAMP to upregulate gap junction coupling has been demonstrated in numerous cell types including ovarian cells (Grazul-Bilska 1996, Luciano et al 2004, Thomas et al 2004. Prolonged coupling of cells in the presence of cAMP has been shown to increase the rate of synthesis of connexin mRNA or to increase stability of the transcript, thereby generating a higher rate of synthesis of gap junction protein available for assembly into new channels (Mehta et al 1992). cAMP is also postulated to induce gap junctional permeability by reapportioning Cx43 from non-junctional sites to junctional plaques at cell-cell interfaces and increase gap junction formation and membrane permeability (Azarnia et al 1981, Atkinson et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al (1992) and Schiller et al (1992) reported that forskolin, an activator of adenylate cyclase, increased Cx43 mRNA 6-fold in a hepatoma cell line, with the increase preceding any detectable increase in dye coupling. Atkinson et al (1995) investigated the exposure of a mouse mammary tumor cell line, MMT22, to 8-bromo-cAMP.…”
Section: Discussionmentioning
confidence: 99%